Pregnant Women's Knowledges, Attitudes, and Practices (KAP) Regarding COVID-19 Prevention - Sirait, Reni Aprinawaty; Susanti, Dewi; Hulu, Victor Trismanjaya (LPPM Universitas Prima Nusantara Bukittinggi, 2024)
Background: Pregnant women have heightened vulnerability during the COVID-19 pandemic due to the need for regular health facility visits for prenatal care and the added responsibility of caring for family members who have contracted COVID-19. The Knowledge, Attitudes, and Practices (KAP) score of pregnant women in relation to COVID-19 prevention can be utilized as input to determine the intervention strategy.Objective: The purpose of this study is to examine the KAP scores of pregnant women. This study employs a quantitative approach and utilizes a descriptive survey methodology.Method: The study included a total of 93 pregnant women who sought medical care at the Pagar Jati Health Center in Deli Serdang Regency in 2022. The sample methodology employed was the method of total sampling. The data collection process involved distributing questionnaires to pregnant women, followed by an analysis that included calculating the frequency distribution of demographic data such as the mother's age, education level, and number of children. Additionally, variables related to the knowledge, attitudes, and practices of pregnant women were also examined.Result: The findings indicated that a majority of individuals possessed inadequate knowledge (62.4%). The predominant sentiment among pregnant women is negative, accounting for 60.2%. A majority of pregnant women (53.8%) fail to adhere to health protocols. Pregnant women between the ages of 20 and 35 exhibit low KAP scores.Conclusion: Similarly, consider the educational attainment of women. Pregnant women with a parity of more than 2 persons also exhibited low KAP scores.